The Impact of Academic Service System Management on Enhancing the Quality of Islamic Elementary Teachers - Imam Sibaweh; Aan Komariah; Diding Nurdin; Nur Aedi (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractThis study aims to investigate the impact of academic service system management on enhancing teacher quality at Al Ihsan Japura Lor Islamic Elementary School, Cirebon. The study focuses on four indicators of academic service system management (efficiency, accessibility, reliability, and technological innovation), as well as four indicators of quality improvement (student satisfaction, learning effectiveness, accreditation improvement, and productivity). The research method uses a quantitative approach with a sample of 33 teachers. The research instrument is a closed questionnaire with tested validity, which is then analyzed using the Pearson product-moment correlation technique. The results of the study indicate that all indicators of academic service system management have a significant effect on improving teacher quality, with correlation values ranging from 0.87 to 0.93, far exceeding the r table value at a significance level of 5%. This finding confirms that an efficient, accessible, reliable, and innovative academic service management system can improve student satisfaction, learning effectiveness, accreditation quality, and teacher productivity in madrasah. This study provides an important contribution to the development of academic management strategies for improving teacher quality, especially in rural community-based madrasahs.Keywords: academic service management, teacher quality, Islamic elementary school. AbstrakPenelitian ini bertujuan untuk menyelidiki dampak manajemen sistem pelayanan akademik terhadap peningkatan kualitas guru di MI Al Ihsan Japura Lor, Cirebon. Penelitian ini berfokus pada empat indikator manajemen sistem pelayanan akademik (efisiensi, aksesibilitas, keandalan, dan inovasi teknologi), serta empat indikator peningkatan kualitas (kepuasan siswa, efektivitas pembelajaran, peningkatan akreditasi, dan produktivitas). Metode penelitian menggunakan pendekatan kuantitatif dengan sampel 33 guru. Instrumen penelitian berupa kuesioner tertutup dengan validitas teruji, yang kemudian dianalisis menggunakan teknik korelasi momen produk Pearson. Hasil penelitian menunjukkan bahwa semua indikator manajemen sistem pelayanan akademik memiliki pengaruh signifikan terhadap peningkatan kualitas guru, dengan nilai korelasi berkisar antara 0,87 hingga 0,93, jauh melebihi nilai r tabel pada tingkat signifikansi 5%. Temuan ini menegaskan bahwa sistem manajemen pelayanan akademik yang efisien, mudah diakses, andal, dan inovatif dapat meningkatkan kepuasan siswa, efektivitas pembelajaran, kualitas akreditasi, dan produktivitas guru di madrasah. Studi ini memberikan kontribusi penting bagi pengembangan strategi manajemen akademik untuk meningkatkan kualitas guru, khususnya di madrasah berbasis komunitas di daerah pedesaan.Kata kunci: manajemen layanan akademik, kualitas guru, Madrasah Ibtidaiyah.